2014
DOI: 10.1097/fjc.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Blockade Improves Left Ventricular Systolic/Diastolic Function and Restores Contractility Reserve in Severe Ischemic Cardiomyopathy in the Mouse

Abstract: IL-1β blockade using a monoclonal antibody in mice with severe LV dysfunction after AMI prevents further deterioration in LV systolic and diastolic function and restores contractile reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…In this model, the benefit appears to be, at least in part, independent of infarct scar size and more directly related to attenuation of ischemic cardiomyopathy. 7 This is in agreement with the literature regarding the beneficial effects of IL-1β blockers in the mouse, 1922 and preliminary data from pilot clinical trials. 6, 23, 24 …”
Section: Discussionsupporting
confidence: 88%
“…In this model, the benefit appears to be, at least in part, independent of infarct scar size and more directly related to attenuation of ischemic cardiomyopathy. 7 This is in agreement with the literature regarding the beneficial effects of IL-1β blockers in the mouse, 1922 and preliminary data from pilot clinical trials. 6, 23, 24 …”
Section: Discussionsupporting
confidence: 88%
“…While the precise mechanisms that orchestrate proinflammatory responses in adult heart failure are not completely understood, it is clear that inhibition of inflammatory cytokine signaling may be beneficial (64). Blockade of IL1β signaling improves LV systolic function and suppresses components of adverse remodeling, including cardiomyocyte hypertrophy and myocardial fibrosis (65)(66)(67)(68)(69)(70). As such, IL1β antagonists are under clinical investigation as novel therapeutics for adults with acute myocardial infarction (MI) and heart failure (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…An early study has found that application of reduced the degree of MI glucocorticoids in dogs due to their anti-inflammatory action, which proves that inflammation has a critical role in MI (3). Subsequent studies have found that macrophages, T lymphocytes, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and IL-6 all have important roles in the area of MI and the deterioration of cardiac function after MI (4)(5)(6). Proinflammatory factors, including TNF-α, IL-1β and IL-6, are not continuously expressed in normal myocardial tissue, and the production or up-regulated expression of these factors represents an internal resistance to myocardial injury (1).…”
Section: Introductionmentioning
confidence: 99%